2017
DOI: 10.1002/rnc.3751
|View full text |Cite
|
Sign up to set email alerts
|

Full‐block multipliers for repeated, slope‐restricted scalar nonlinearities

Abstract: Summary This paper provides a comprehensive treatment of full‐block multipliers within the integral quadratic constraints framework for stability analysis of feedback systems containing repeated, slope‐restricted scalar nonlinearities. We develop a novel stability result that offers more flexibility in its application because it allows for the inclusion of general Popov and Yakubovich criteria in combination with the well‐established Circle and Zames‐Falb stability tests within integral quadratic constraint th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 71 publications
(194 reference statements)
0
35
0
Order By: Relevance
“…In [21], [4], it has been shown that their relative performances vary with different examples. It must be highlighted that results in the basis functions can be significantly improved by manually selecting the parameters of the basis [14], [15]. Similarly, manual tuning of delta functions can be useful for time-delay systems [22].…”
Section: A Oveview Of Searches Of Zames-falb Multipliers In Continuomentioning
confidence: 99%
“…In [21], [4], it has been shown that their relative performances vary with different examples. It must be highlighted that results in the basis functions can be significantly improved by manually selecting the parameters of the basis [14], [15]. Similarly, manual tuning of delta functions can be useful for time-delay systems [22].…”
Section: A Oveview Of Searches Of Zames-falb Multipliers In Continuomentioning
confidence: 99%
“…A unified framework has been proposed in (Jönsson and Rantzer, 2000) for the search of multipliers. Recently, Fetzer and Scherer (2017a) proposed a comprehensive analysis for the case of slope restricted nonlinearities in discrete time is presented, showing that the stability test in the literature are related.Consequently, IQCs have been widely used to perform stability and robustness analyses of dynamic systems (D'Amato et al, 2001;Heath and Li, 2010;Fetzer and Scherer, 2017b) in the frequency domain as well as in the time-domain employing dissipativity theory (Brogliato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Notable achievements are the small gain theorem , which underpins the robust control literature and the passivity theorem and related results . In addition, other researchers have considered the case when one of the systems in the feedback interconnection was linear and this has yielded a number of absolute stability results such as the popular Circle and Popov criteria, and also the theory associated with Zames‐Falb multipliers …”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, other researchers have considered the case when one of the systems in the feedback interconnection was linear and this has yielded a number of absolute stability results such as the popular Circle and Popov criteria, and also the theory associated with Zames-Falb multipliers. [5][6][7][8] The circle criterion originally arose in the two-part paper of Zames,9,10 where the stability of systems of the form depicted in Figure 1 was studied. In most applications of the Circle Criterion, the troublesome nonlinearity, Δ, is considered to be static with a graph belonging to a particular sector.…”
Section: Introductionmentioning
confidence: 99%